Successful triple therapy for advanced synchronous multiple primary esophageal carcinoma with metal stenting, photodynamic and comprehensive systemic therapies—shining light on hope: a case report and literature review - Zou, Dan; Yan, Ying; Li, Yifan; Ma, Huanhuan; Bai, Yuping; Wang, Xueyan; Wang, Bofang; Wang, Yunpeng; Ma, Jingwei; Chen, Hao (Frontiers in Immunology, 2025)
Synchronous multiple primary esophageal cancer (SMPEC) is a rare and aggressive condition often accompanied by obstructive dysphagia, significantly impacting patients’ quality of life. Current treatments, including chemotherapy, radiotherapy, immunotherapy, and targeted therapy, are limited in providing immediate symptom relief. This case report describes a 64-year-old female with SMPEC and metastases to thoracic lymph nodes, the lesser curvature of the stomach, and the right adrenal gland, presenting with severe dysphagia (score 4 on the Japanese Dysphagia Severity Scale). To rapidly alleviate symptoms, she underwent simultaneous metal stent implantation and photodynamic therapy (PDT). She started a liquid diet on the second day after treatment and resumed a normal diet one week later. Subsequently, she underwent systemic chemotherapy, targeted therapy, and immunotherapy. By the third treatment cycle, primary and metastatic lesions significantly decreased, achieving a partial response (PR) with stable disease and progression-free survival (PFS) exceeded 12 months. This triple therapy approach—combining stent implantation, PDT, and systemic treatments—proved effective and safe for advanced SMPEC, not only providing immediate dysphagia relief and selective tumor destruction but also delaying disease progression and improving patient outcomes.